AVALIAÇÃO DO POTENCIAL ANTICARCINOGÊNICO DO LÁTEX DE SYNADENIUM GRANTII HOOK F. EM DROSOPHILA MELANOGASTER - BELFORT, Gabriel Ribeiro; GUTERRES, Zaira da Rosa; GARCEZ, Walmir Silva; SOARES, Luzinátia Ramos; GOUVEIA, Juceli Gonzalez (ANAIS DO ENIC, 2022)
-